Pengaruh Kompensasi terhadap Kinerja Karyawan di Perusahaan Jasa Pengiriman di Kota Serang Indonesia - Didi Wandi; Heri Sapari Kahpi; Fidziah Fidziah; Zaenal Abidin (Research Center and Case Clearing House PPM School of Management, 2022)
Compensation is one of the most important aspects for employees and organizations. Can give compensation or remuneration based on individual, group, and company performance as a whole to improve employee performance and ultimately achieve organizational goals. This study aims to determine the effect of financial and non-financial compensation on the performance of employees of freight forwarding services in the city of Serang, Indonesia. The sample in this study amounted to 90 employees. The method used is the quantitative method. The data collection technique used was a questionnaire. Data analysis used multiple linear regression. The results show partially that financial compensation has a positive and significant effect on employee performance, and non-financial compensation has a positive and significant impact on employee performance. Simultaneously, financial and non-financial compensation affects employee performance.